Recent trends in reproductive tourism and international surrogacy: ethical considerations and challenges for policy - Deonandan R (Dove Medical Press, 2015)
Raywat Deonandan Interdisciplinary School of Health Sciences, University of Ottawa, Ottawa, ON, Canada Abstract: Reproductive tourism, or “cross-border reproductive care”, is the phenomenon of people crossing international borders to access reproductive technologies. One of the fastest-growing categories of cross-border reproductive care is international surrogacy, the act of infertile clients traveling internationally to engage the paid services of foreign surrogates to carry their babies to term. It is a multibillion-dollar global industry presenting unique legal, ethical, and risk-management challenges. Clients tend to be price-sensitive, middle-income individuals seeking services from surrogates who in the global market are thought to be of quite low socioeconomic status. Risks are experienced by all parties involved in the transaction, including the client’s countries of origin and destination. The risks to the surrogate evolve from the potential to exploit her economic vulnerability in order to encourage both consent and unfair pricing. Opportunities for policy development are explored. Keywords: surrogacy, assisted reproduction, medical tourism, IVF, ART, gestation